Bonding Characterization Between 316L and Porous Stainless Steel Pipes by Vacuum Brazing. Issue 2 (February 2018) - Yaning, Li; Xinting, Kang; Jian, Wang; Huiping, Tang
Abstract: Vacuum brazing between porous stainless steel (PSS) tube and 316L stainless steel has been performed using BNi-7 brazing paste as a filler metal. And the interface microstructure of the joint was analyzed by SEM and EDS. The results show that Ni(Cr, Fe)-P intermetallic compounds and chromium-rich nickel-iron-based solid solutions phases are the main phases in the brazing seam. The wettability of the molten braze alloy to PSS is better than that to 316L. The molten braze filler is pulled into the pore of PSS by a capillary action during brazing. The highest tensile strength of 245 MPa is acquired from the joint brazed at 980°C for 15 min. Longer processing time or higher processing temperature does not improve the joint strength further.